Production of Structured RNA Fragments by In Vitro Transcription and HPLC Purification. Issue 6 (17th June 2021) - Karlsson, Hampus; Feyrer, Hannes; Baronti, Lorenzo; Petzold, Katja
Abstract: The understanding of the functional importance of RNA has increased enormously in the last decades. This has required research on the RNA molecules themselves, with the concomitant need for obtaining purified RNA samples, such as for structural studies by NMR or other methods. The main method to create labeled and unlabeled RNA, T7 in vitro transcription, suffers from sequence‐dependent yield and often low homogeneity for short constructs (<100 nt) and requires laborious purification. Additionally, the design of structured RNA fragments mimicking the structure of a larger biological RNA is often not straightforward. Secondary structure simulations can be used to make reliable predictions about the folding of a particular RNA fragment. In this article, we describe how to design an RNA construct of interest from a larger sequence, and we combine several previously published improvements of the in vitro transcription method, such as the use of 2′‐methoxy modifications and dimethyl sulfoxide or the use of tandem repeats, to increase yield and purity of in vitro–transcribed RNA. Together with a high‐performance liquid chromatography (HPLC) purification procedure using both reversed‐phase ion‐pairing and ion‐exchange HPLC, we provide a robust protocol to obtain highly pure RNA of short to intermediate length in large quantities. The protocol optimizes yield, especially for RNA starting with nucleotides other than G. At the same time, it is simplified, and the required time is reduced. The protocols described here constitute a versatile pipeline for the production of purified RNA samples and are suitable for users with little experience in liquid chromatography. © 2021 The Authors. Basic Protocol 1 : RNA construct design Basic Protocol 2 : DNA template production and in vitro transcription Alternate Protocol : Tandem transcription and RNase H cleavage Basic Protocol 3 : Reversed‐phase ion‐pairing HPLC purification Basic Protocol 4 : Ion‐exchange HPLC purification